Abdul Kahar Muzakir: Bersama Emas dari Timur Jawa Menembus Pasar Internasional - Kharisma Rostia Fitri (PT Inovasi Penelitian Terpadu, 2025)
Tobacco plantations in Jember began before 1850 along with other areas in the Dutch East Indies that planted commodities such as coffee, sugar cane, rubber, and indigo. In line with the changing politics and economy in the Netherlands, it provided opportunities for private companies to open businesses related to plantations. At that time, the tobacco plantation business grew rapidly thanks to the agrarian law of 1870 where the Dutch gave permission to entrepreneurs to manage land for 75 years. The commodities chosen at that time were commodities that had the potential for high selling value in the international market. Tobacco, which is the ingredient for making cigars, became a leading product from the Deli region in North Sumatra, Klaten in Central Java, and Besuki in East Java. The very profitable tobacco export process encouraged the growth of this industry and had a significant impact on economic growth in the area. In the 1800s, smoking cigars was a common habit, while cigarettes were still relatively rare at that time. A famous poem entitled